Importance of Diakonoff’s Research in Recognition of the Median Period in Iran - MORADI, Maryam; ALILOO, Sara (Historia i Świat, 2021)
The history of the Median period written by Igor Mikhailovich Diakonoff (published in 1956) was translated to Persian by Karim Keshavarz in 1345 Solar year. This book was the product of profound and insightful research of this author that had been done by the request of Azerbaijan Science Academy in that time and its importance at the time of its publication and translation was immense as there had been no single book or other research publication directly covering this period in the Persian literature before. The available historical or archeological information on this period was only limited to the notes of Greek historians and some new western resources. Although those sources were valuable, they could not fill the vacant place of rigidly and accurately written resources for other researchers of this period because they were not based on direct data i.e. scripts, tablets and other archaeological data found during relevant excavations. The difference between Diakonoff’s research and other resources is that he first gives comprehensive information concerning resources from this period, then fully assesses them, and additionally describes the geographical and historical aspects. This makes Diakonoff’s Median book an exceptionally accurate resource in this regard and therefore even after several decades it still remains so important in Iranology and cognition of Iranians. In fact, one can see the immense impact of Diakonoff’s research on the field of the Median history since the translation time until the present time. It has always been one of the main sources cited in historical, linguistic, ethnological, archaeological and interdisciplinary studies by Iranian researchers.